Externalities and the Allocation of Decision Rights in the Theory of the Firm - Helmut Bester (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
This paper views authority as the right to undertake decisions that have external effects on other members of the organization. Because of contractual incompleteness, monetary incentives are insufficient to internalize these effects in the decision maker's objective. The optimal assignment of decision rights minimizes the resulting inefficiencies. We illustrate this in a principal-agent model where the principal retains the authority to select 'large' projects but delegates the decision right to the agent to implement 'small' projects. Extensions of the model discuss the role of effort incentives, asymmetric information and multistage decisions.
urn:nbn:de:bvb:19-epub-13525-5
Keywords: D23; D82; L22; 330; Authority; Control Rights; Decision Rights; Delegation; Externalities; Incomplete Contracts; Theory of the Firm